The extent of computer- based accounting system use in manufacturing companies - a preliminary study of manufacturing companies in Kuching, Sarawak /Corina Joseph and Tamoi Janggu (Universiti Teknologi MARA, Sarawak, 2004)
The rapid advancement in information and communication technology (ICT) and the globalisation of business call for serious changes to be implemented in order to strengthen the accounting profession The new-millennium accountant must have a high level of competency in ICT in order to be conversant with global business practices and provide relevant, effective and value-added services (MIA, 2001). This directly has a significant impact on the manufacturing industry in Malaysia, which has been identified as one of the major sectors contributing to growth during the Eighth Malaysia Plan (8MP). This study reports on the extent of computerized based accounting system (CBAS) use among the manufacturing companies in Kuching, Sarawak. This study is conducted through a questionnaire survey method. Generally, the study concludes that the average adoption rate (52%) among the respondents is due to the small size of the majority of the respondent companies, lack of exposure and awareness, attitude problem, business's needs and requirement and others. Some recommendations have been made to improve the existing scenario. They include increase awareness especially among the small companies, implement more stringent policy for certain procedures to increase high usage of CBAS and review the existing accounting curriculum especially pertaining to the computerized accounting area.